Divergent perceptions of new marine protected areas: Comparing legal consciousness in Scilly and Barra, UK. (January 2016) - Pieraccini, Margherita; Cardwell, Emma
Abstract: The legal establishment of protected areas is often associated with a situation of conflict arising between conservation and other human activities in particular spaces. This is primarily due to the fact that protected areas law requires changes in the behaviour of resource users. Conservation conflicts arising from the establishment of protected areas are well documented in the social science literature and attempts are made to find ways to reduce such conflicts. Yet, what of cases in which the establishment of protected areas serves to officialise existing sustainable practices and may contain an element of future proofing? Do they still generate practices of resistance and conflict? These questions are answered in this paper comparing two case studies where the authors conducted primary qualitative research: the designation of new Marine Conservation Zones under the Marine and Coastal Access Act 2009 in the Isles of Scilly (South West of England) and the designation of a new Special Area of Conservation under Council Directive 92/43/EEC (the Habitats Directive) in Barra (Scottish Outer Hebrides). Both protected areas are highly unlikely to impose changes in local sea-users' behaviour, as in both cases they validate existing practices and are future proofing, in the sense that they offer tools that can be used to minimize the effects of potential future shocks and stresses, presently unknown. Yet, while in Scilly the new Marine Conservation Zones have been perceived as a positive addition to the seascape, in Barra the Special Area of Conservation has been heavily contested by the local community. The islanders' different perspectives towards protected areas law can be described as divergent 'legal consciousness'. 'Legal consciousness' is a socio-legal concept concerned with the ways in which the law is experienced, interpreted and re-shaped by ordinary people. In our case studies, legal consciousness is a dependent variable, being the product of three main causes: history, power relationships between regulators and regulatees and risk. Highlights: Stakeholder perceptions of MPA designation provide important insights into MPA acceptance. The socio-legal concept of legal consciousness is useful in understanding stakeholder perceptions. A case study comparison highlights differences in attitudes towards MPA designation in the UK.